1996
DOI: 10.1021/ja9538039
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanistic Pathways for Zirconium-Catalyzed Carboalumination of Alkynes. Requirements for Cyclic Carbometalation Processes Involving C−H Activation

Abstract: The reactions of internal and terminal alkynes with organoalanes containing Et, n-Pr, and i-Bu groups in the presence of Cp2ZrCl2 and MeZrCp2Cl were investigated with the goal of clarifying mechanistic details of some representative cases. Three fundamentally different processes, i.e., (i) C−M bond addition without C−H activation in the alkyl group, (ii) cyclic C−M bond addition via C−H activation, and (iii) hydrometalation, have been observed, and the courses of these reactions significantly depend on (i) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(97 citation statements)
references
References 31 publications
2
91
0
3
Order By: Relevance
“…We believe that both the discovery of the Dzhemilev ethylmagnesiation and our mechanistic clarification 22 have not only clearly established the existence of both acyclic and cyclic carbozirconation processes but also alerted us to sharply and carefully distinguish some seemingly analogous carbometalation reactions of zirconocene derivatives. We were later further surprised by the existence of bimetallic (involving both Zr and Al) cyclic carbozirconation of alkynes and alkenes that may be viewed as a hybrid of acyclic and cyclic carbozirconation 23 (Scheme 3). We also noted that our bimetallic (Zr-Al) cyclic carbozirconation process closely resembled the corresponding carbotitanation of alkenes with titanium-carbene species that can be viewed as a two-membered titanacycle (Tebbe reagent) generated from a Ti-Al bimetallic system.…”
Section: Historical and Mechanistic Background Of Carbometalation Of mentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that both the discovery of the Dzhemilev ethylmagnesiation and our mechanistic clarification 22 have not only clearly established the existence of both acyclic and cyclic carbozirconation processes but also alerted us to sharply and carefully distinguish some seemingly analogous carbometalation reactions of zirconocene derivatives. We were later further surprised by the existence of bimetallic (involving both Zr and Al) cyclic carbozirconation of alkynes and alkenes that may be viewed as a hybrid of acyclic and cyclic carbozirconation 23 (Scheme 3). We also noted that our bimetallic (Zr-Al) cyclic carbozirconation process closely resembled the corresponding carbotitanation of alkenes with titanium-carbene species that can be viewed as a two-membered titanacycle (Tebbe reagent) generated from a Ti-Al bimetallic system.…”
Section: Historical and Mechanistic Background Of Carbometalation Of mentioning
confidence: 99%
“…It was indeed this surprising finding that led to the clarification and establishment of the bimetallic cyclic mechanism for carbozirconation of alkynes mentioned earlier (Scheme 3). 23 Fortunately, we soon learned that the use of more polar solvents including CH 2 Cl 2 , CH 3 CHCl 2 , and (CH 2 Cl) 2 almost totally suppressed the undesired cyclic carbometalation process thereby promoting formation of the desired products (Scheme 6).…”
mentioning
confidence: 99%
“…A later report (30) on a closely related reaction with ''cationic'' chiral zirconocene derivatives should be noted. Clearly, from the results presented above, the Zr-catalyzed carbometallation is multimechanistic (23,(31)(32)(33)(34)(35)(36) and sensitive to several critical factors including ligands (22), solvents (23), and metal countercations of alkylmetals. With respect to metal countercations, the following generalizations may be presented as useful guidelines (36).…”
Section: Design Of Protocolsmentioning
confidence: 99%
“…It was suggested that complex 11A is the precursor of intermediate 11 [10] or they exist in dynamic equilibrium with each other [13]. The structure 11A also can be represented as η 2 -ethylene interaction with zirconium atom (complex 11B, Scheme 5) Thus, before our study there were no comprehensive answers on question how the probable key intermediates interact with the alkenes of various structures and regulate the reaction chemo-and regioselectivity.…”
Section: A 11bmentioning
confidence: 93%
“…Experimental study on the mechanism of catalytic cycloalumination of alkynes [10] and alkenes [11] showed that the active site of the reaction is cyclic five-membered bimetallic Zr,Al-complex 11 (Scheme 5), which is fully converted to the target aluminacycles when treated with substrate. Earlier the intermediate 11 was found in the system Cp 2 ZrCl 2 -AlEt 3 by W. Kaminsky [12].…”
Section: Introductionmentioning
confidence: 99%